2020
DOI: 10.1186/s12890-020-1157-3
|View full text |Cite
|
Sign up to set email alerts
|

How people with chronic obstructive pulmonary disease perceive their illness: a qualitative study between mind and body

Abstract: Background Although many studies on people with Chronic Obstructive Pulmonary Disease (COPD) have examined the mutual impact of physical status and emotional experience, there is limited knowledge about the way COPD people first-hand perceive their condition. This study was designed to investigate the illness perceptions of the patients and, secondarily, to explore their beliefs about the mind-body relationship. Methods This qualitative study has e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 32 publications
(35 reference statements)
2
6
0
2
Order By: Relevance
“…Limited abilities became a struggle between wanting to and not being able to do things. This aligns with earlier research showing that a lot of time was consumed by waiting for their body to be able to function [40, 41]. People with COPD expressed trying to endure living with the consequences of breathlessness, use positive psychological coping strategies and accepting loss of independence [2, 42–44].…”
Section: Discussionsupporting
confidence: 85%
“…Limited abilities became a struggle between wanting to and not being able to do things. This aligns with earlier research showing that a lot of time was consumed by waiting for their body to be able to function [40, 41]. People with COPD expressed trying to endure living with the consequences of breathlessness, use positive psychological coping strategies and accepting loss of independence [2, 42–44].…”
Section: Discussionsupporting
confidence: 85%
“…This was most profound during disease exacerbations. Similar to our ndings, previous studies have also indicated that ongoing respiratory symptoms lessened the quality of life for those with COPD, varying by disease severity (22,23). In addition, participants complained of the direct and indirect costs of medications, especially since symptoms did not improve with their use.…”
Section: Social and Religioussupporting
confidence: 88%
“…The majority of patients of the experimental group found the strategies to overcome the difficulties related to the NIV's usage (i.e., mask fit, air leakage, and claustrophobia), thanks to the psychological intervention, which integrated them into their healthcare routine. These results stress the relevance of paying attention to the patients' needs during the adaptation to a new device process that is suddenly perceived as another sign of limitation (67). Indeed, expectations are driven by not only medication but also the disease itself and the elaboration process of the information collected by the patients about it (68,69).…”
Section: Discussionmentioning
confidence: 75%